(untitled) (Sains Humanika, 2021)
The study investigates the relationships between job designâ€™s task characteristics and knowledge creation process (SECI). The implication of job design in improving work productivity and performance has been extensively reported in various studies. However, only slight attention was given concerning the relationship between job design characteristics and knowledge creation process. Using the survey research methodology involving the Administrative and Diplomatic Officers working in several Malaysian federal ministries, the study found that the six independent variables of task characteristics have significant relationships with SECI. The findings suggest the importance of well-designed task characteristics in supporting the creation of knowledge within the federal ministries. The present study should capture the interest of both researchers and practitioners as it has developed an empirical-based framework linking task characteristics and SECI.Â Â